2014
DOI: 10.1002/adma.201304366
|View full text |Cite
|
Sign up to set email alerts
|

Physically Flexible, Rapid‐Response Gas Sensor Based on Colloidal Quantum Dot Solids

Abstract: A gas sensor based on PbS colloidal quantum dots (CQDs) is constructed on a paper substrate, yielding flexible, rapid-response NO₂ gas sensors, fabricated from the solution phase. The devices are highly sensitive and fully recoverable at room temperature, which is attributed to the excellent access of gas molecules to the CQD surface, realized by surface ligand removal, combined with the desirable binding energy of NO₂ with the PbS CQDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
249
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(254 citation statements)
references
References 38 publications
3
249
0
2
Order By: Relevance
“…A wide range of doping strategies have shown both doping polarities in PbS QDs 116 , making it a versatile sensitizing system to combine with any channel material. Solution-processed CQD optoelectronic devices have already demonstrated compatibility with CMOS technology 117,118 and flexible device concepts 119,120 .…”
Section: Ideal Sensitizer Characteristicsmentioning
confidence: 99%
“…A wide range of doping strategies have shown both doping polarities in PbS QDs 116 , making it a versatile sensitizing system to combine with any channel material. Solution-processed CQD optoelectronic devices have already demonstrated compatibility with CMOS technology 117,118 and flexible device concepts 119,120 .…”
Section: Ideal Sensitizer Characteristicsmentioning
confidence: 99%
“…In that work different additives, such as Brought to you by | MIT Libraries Authenticated Download Date | 5/9/18 10:39 AM Synthesized PbS nanoparticulate thin films for a rapid NO 2 gas sensor 205 organic substances were introduced into the reaction bath in order to improve sensitivity of the sensing device [21]. Recently Liu et al reported physically flexible and fast response gas sensor based on colloidal PbS quantum dots, having response time of 4 s [22]. This device consisted of a paper on which PbS quantum dots were spin coated and it worked at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the fi elds of medical [ 7 ] and consumer electronics [ 8 ] benefi t from the variety of already available fl exible devices including electrode arrays, [ 9,10 ] solar cells, [ 11 ] diagnostic devices, [12][13][14][15] displays, [ 16 ] memory elements, [ 17,18 ] and various types of sensors. [19][20][21][22][23][24] At the moment, postprocessing, e.g., signal amplifi cation, or multiplexing of the data acquired by entirely fl exible and even imperceptible devices, [ 5,[25][26][27][28] such as pressure, [ 11,29,30 ] temperature, [ 26,30 ] encephalography, [ 7,27 ] or magnetic fi eld [ 22,24,25 ] sensors, is done using external rigid electronics. The connection between the fl exible and the rigid parts of the measurement system is established using cables.…”
Section: Doi: 101002/aelm201600188mentioning
confidence: 99%